Influences of pH, Temperature, and Moisture on Gaseous Tritium Uptake in Surface Soils - Fallon, Robert D. (1982)
In South Carolina surface soils, the uptake of gaseous tritium (T(2), HT, or both) showed a broad optimal temperature response from about 20 to 50°C, with the highest rates at 35 to 45°C. The optimal pH was in the range of 4 to 7. Uptake rates declined at the wet and dry extremes in soil moisture content. Inhibition seen upon the addition of hydrogen or carbon monoxide to the soil atmosphere suggested that hydrogenase may be responsible for T(2)-HT uptake in soil. During the period of most rapid recovery in a 36-day incubation of reinoculated, sterilized soil, T(2)-HT uptake rates doubled every 2 to 4 days. Thus, T(2)-HT uptake appears to be biologically mediated. Soil uptake of T(2)-HT was not severely limited by pH, temperature, or moisture in the soils tested. Thus, rapid exchange of gaseous tritium into soil water must be expected and accounted for in modeling the isotope distributions around nuclear facilities.